All Days 1999
DOI: 10.2118/54481-ms
|View full text |Cite
|
Sign up to set email alerts
|

Development of Welding Procedure Specification for Girth Welds in Coiled Tubing

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractAs oil and gas well servicing operations involve increasingly larger coiled tubing (CT) sizes, the ability for extending their useful or working life becomes of increasingly greater economic importance. Not only do larger tubing sizes exhibit inherently lower fatigue lives, but also their replacement cost is considerably greater. Efforts are underway elsewhere for developing CT repair strategies for recovering some of the CT fatigue life that has been reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The weld metal showed coarse granular bainite with the average grain size of 33.8 µm in diameter (Figure 3c), but the structure was finer than that produced by gas tungsten arc welding process, because plasma arc welding process provides focused heat transfer that results in a lower heat input leading to improved penetration in the smaller heat-affected zone [32]. Previous studies observed fatigue fractures at the softened HAZ [5,6]; however, the inferior coarse WJ microstructures with low hardness produced using a welding consumable with low strength or a process with high heat input can cause fatigue fracture [3,4].…”
Section: Microstructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The weld metal showed coarse granular bainite with the average grain size of 33.8 µm in diameter (Figure 3c), but the structure was finer than that produced by gas tungsten arc welding process, because plasma arc welding process provides focused heat transfer that results in a lower heat input leading to improved penetration in the smaller heat-affected zone [32]. Previous studies observed fatigue fractures at the softened HAZ [5,6]; however, the inferior coarse WJ microstructures with low hardness produced using a welding consumable with low strength or a process with high heat input can cause fatigue fracture [3,4].…”
Section: Microstructuresmentioning
confidence: 99%
“…For practical application, steel parts are usually joined by welding, which can introduce residual stresses and heterogeneous microstructures [1,2] that can result in locally inferior mechanical properties compared to the base material. For example, the fatigue life of welds is shorter than that of the base material due to welding defects [3,4] or heat-affected zone (HAZ) softening [5,6], where fatigue fracture occurs in these regions. Low-carbon steels are readily joined with several common fusion welding processes such as plasma arc welding (PAW) and gas tungsten arc welding (GTAW), but some studies [7][8][9] reported that friction stir welding process as an solid state welding showed superior fatigue strength due to the synergetic effect of microstructure, superior tensile properties and favorable residual stress, which inhibit the growth of cracks compared to other joints.…”
Section: Introductionmentioning
confidence: 99%
“…butt welding of plate, tube forming welding and butt welding of coiled tubing on site. For CT80 tubing, the strength is high and the wall thickness is thin, the steel is made through TMCP process, and the crystal granular of steel is fine, gas tungsten arc welding (GTAW) welding method is generally used [3,4,5,6]. The working condition of coiled tubing is special, high strength and high plasticity is also demanded for the welded joint.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the present welding method has severe limitations in field application. Also there is a correlation between the quality and repeatability of the welds and the skill of the welding operator [2].…”
Section: Introductionmentioning
confidence: 99%